A generalized measure of competition - Riccardo Cesari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
Using the conditional probability of the passage of customers from one firm to another, a new, implementable measure of market competition is obtained which generalizes the classical Hirschman-Herfindhal index.
Keywords: 330